Prosecutorial Discretion and the Death Penalty: An Integral Perspective - Mangino, Matthew T.; Champion, David R. (International Journal of Criminology and Sociology, 2013)
The prosecutor’s choice to pursue the death penalty is one of the most momentous decisions he or she will face. Capital punishment represents the ultimate power of the state over its citizenry, and the decision to take the life of an offender is fraught with moral complexity. This paper reviews some of the extant literature on the US death penalty in general and the particular issue of decision-making for prosecutors. Further, we introduce discussion on how Wilber’s Integral theory might be applied to the topic. We present aspects of Integral theory, including the four quadrant model and what Wilber refers to as the Basic Moral Intuition (BMI), as possible tools that may be used to navigate the ethical difficulties surrounding this decision-making process. We anticipate that delving into aspects of the Integral theory and contemplating on how they relate to concrete issues of criminal prosecution may assist CJ practitioners in how they might find pathways to resolutions of ethical quandaries.